Quality Improvement of Higher Education Viewed From Management, Quality Audit, and Training - Slameto, Slameto (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to identify the determinant variables of Higher Education quality: Higher Education management, the role of internal quality auditors, and education and training. This research was conducted based on the perception of stakeholders from 5 private Universities (4 Universities in West Java and 1 University in Papua, Indonesia). The ordinal scale used in this study is a Likert Scale, which consists of 20 items, which are proven valid (validity scores . 225 to.792) with a reliability index of Cronbach Alpha = .830. Data were analyzed by multiple linear regressions using the Stepwise Model SPSS program of version 25. The results of this study indicate that the average of almost all variables is between moderate and high. This research succeeded in finding 2 determinant models of Higher Education quality improvement. Higher Education management cycle should focus on internal quality auditors, starting from planning, budgeting, organizing and controlling.